Structural diversity and magnetic properties of four Cu(II)/Co(II) coordination complexes based on 3, 5-bis(2-carboxylphenoxy)benzoic acid. (15th February 2018) - Fan, Liming; Gao, Lingling; Wang, Xiaoqing; Wang, Jiang; Zhao, Li; Fang, Kegong; Hu, Tuoping
Graphical abstract: Four Cu(II)/Co(II) coordination complexes based on 3, 5-bis(2-carboxylphenoxy)benzoic acid with antiferromagnetic or spin transition behaviors. Abstract: Four coordination complexes, namely, [Cu(HBCB)] n (1 ), [Cu(HBCB)( o -bimb)]·H2 O (2 ), [Cu1.5 (BCB)( m -bimb)1.5 ]·DMF n (3 ), and [Co1.5 (BCB)(bpy)1.5 (H2 O)] n (4 ), have been assembled from the semirigid tripodal 3, 5-bis(2-carboxylphenoxy)benzoic acid (H3 BCB) in the presence or absence of the N-donors ( o -bimb = 1, 2-bis(imidazol-1-ylmethyl)benzene, m -bimb = 1, 3-bis(imidazol-1-ylmethyl)benzene, bpy = 4, 4′-bipyridine). Structural analyses revealed that complex1 features a Cu2 (COO)4 SBUs based 3D (3, 6)-connected 4·6 2 2 4 2 ·6 10 ·8 3 -rtl net. Complex2 displays an interesting coordination molecule cage structure. Complex3 exhibits a 2D (3, 4, 4)-connected 4·6 2 2 4·6 4 ·82 6 4 ·8 2 sheet. And complex4 shows a 3D (3, 4, 6)-connected 5·6 2 2 5 6 ·6 4 ·7·8 2 ·9 2 6 4 ·8·9 net based on the binuclear Co2 (COO)2 SBUs and Co2 ions. The temperature-dependent magnetic susceptibilities indicated there are gradual spin transition behavior in1, and antiferromagnetic interactions in4 .